Modified high-efficiency carbon material for deep degradation of phenol by activating persulfate. (July 2022) - Yang, Lixi; Yin, Defeng; Zheng, Yanxia; Yang, Yubo; Li, Yuchao; Hao, Jinguo; Ai, Bing; Ge, Tingting; Zuo, Cuncun; Wang, Xiaobin; Wang, Qian; Wang, Ming; et al.
Abstract: A series of cobalt-nitrogen modified catalysts were prepared and applied to the degradation of phenol. The Mott Schottky catalyst (CoO/NGr@C) with high pyridine nitrogen content was designed to activate potassium peroxodisulfate (PDS) to generate active free radicals for phenol degradation. The structural properties of the materials are analyzed by XPS, TEM and then the charge density calculation is performed by DFT, which proves the existence of the highly active interface effect. Co–N-CMCM-41 can only degrade phenol into benzoquinone and it is difficult to achieve further degradation of benzoquinone, while the modified CoO/NGr@C can achieve deep mineralization of the intermediate benzoquinone through UV spectrum. EPR was used to prove that both hydroxyl radicals and sulfate radicals exist in the degradation process of phenol. Through the DFT simulation calculation of the material, it is proved that the existence of carbon activated by nitrogen and the electron rearrangement between cobalt and nitrogen-rich carbon lead to the catalytic activity of the material. The degradation conditions of phenol were optimized and the reaction kinetics of further phenol degradation were studied. The activation energy of phenol degradation on CoO/NGr@C is calculated to be 34.38 kJ mol −1 . Graphical abstract: Image 1 Highlights: Cobalt nitrogen modified catalyst with high pyridine nitrogen content. Highly active Mott Schottky interface catalyst for phenol oxidation. Catalytic reaction mechanism based on DFT and EPR analysis. Degradation process of phenol and intermediates. Reaction kinetics of phenol degradation including degradation of β-benzoquinone.